(3GdJbOeI aj TQM GdebOeIs - (3LHQjd Hf MSf Hf YKeGf Hf eMehO Hf YKeGf GdcfLGfis; (3CHh GddjK GdSeQbfOj , GeGe GdgOj,J (B373 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdebOeI GdefShHI Edi GdEeGe Gdabjg CHhGddjK hbO SeGgG GdebOeI hSejJg HcJGH GdJbOeI aj TQM GdebOeI s
(3BNQgG (B:s
(3Cf CTQM dg gPG GdcJGH ahLOJ Pgfg ehRhfkG Je HGdNjQ hMSf GdebGe s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B91s
Keywords: (3Gdabg GdMfajs